Agesilaou, Andria - (:unkn) unknown (My University, 2026)
Ph.D. student at the Department of Communication and Internet Studies of the Cyprus University of Technology. My research interests focus on the investigation of new technologies and teaching methods. More specifically, my reaserch interests include Gamification in education, game-based learning and augmented reality applications in education.. In my leisure time, I enjoy travelling and exercising.